মুক্তিযুদ্ধে মেজর হায়দার ও তাঁর বিয়োগান্ত বিদায় - ইসলাম, জহিরুল
Articles chiefly on role and contribution of Ābu Tāhera Mohāmmada Hāẏadāra, 1942-1975, Sector Commander of Bangladesh Army, in 1971 liberation movement of Bangladesh.